2023
DOI: 10.1097/js9.0000000000000632
|View full text |Cite
|
Sign up to set email alerts
|

Techniques of staging laparoscopy and peritoneal fluid assessment in gastric cancer: a systematic review

Abstract: Background: Staging laparoscopy for gastric cancer is recommended to assess the tumor’s locoregional extension and exclude peritoneal disease. As there is no consensus on optimizing the procedure’s diagnostic accuracy, we aimed to systematically review the literature on operative techniques, followed by peritoneal lavage fluid assessment in gastric cancer patients. Specifically, we sought to indicate the most common characteristics of the procedure and cytological evaluation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 201 publications
0
2
0
Order By: Relevance
“…Pos-sibly, with the advancement of computing power and graphic processing technologies [53], artificial intelligence (AI) techniques demonstrate the potential to enhance CT by providing more accurate staging and restaging of the GC along with improved detection of recurrence and progression of the disease [54]. To address shortcomings of CT, staging laparoscopy (SL) is a recommended complementary diagnostic method in potentially resectable GC, preventing 25% of irrelevant gastrectomies [14,55]. Although SL has limited abdominal cavity exploration, the procedure yield exceeds 36%, with lavage cytology further improving the detection of radiologically occult peritoneal metastasis [56,57].…”
Section: Radiological Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…Pos-sibly, with the advancement of computing power and graphic processing technologies [53], artificial intelligence (AI) techniques demonstrate the potential to enhance CT by providing more accurate staging and restaging of the GC along with improved detection of recurrence and progression of the disease [54]. To address shortcomings of CT, staging laparoscopy (SL) is a recommended complementary diagnostic method in potentially resectable GC, preventing 25% of irrelevant gastrectomies [14,55]. Although SL has limited abdominal cavity exploration, the procedure yield exceeds 36%, with lavage cytology further improving the detection of radiologically occult peritoneal metastasis [56,57].…”
Section: Radiological Evaluationmentioning
confidence: 99%
“…Moreover, SL maintains its sensitivity independently of lymph node involvement, and its yield has remained consistent over time despite improvements in imaging techniques. A recent Systematic Review indicated a high heterogeneity in procedure technique [55], and there is no consensus on whether to perform repeated SL after NAC as well. However, given the increased rate of minimally invasive gastrectomy in the West, performing laparoscopy with intraoperative decision to pursue with curative intent gastrectomy, may condition further assessment of surgical textbook outcomes.…”
Section: Radiological Evaluationmentioning
confidence: 99%